The politics of evidence in online illness narratives: An analysis of crowdfunding for purported stem cell treatments. (July 2019) - Tanner, Claire; Munsie, Megan; Sipp, Doug; Turner, Leigh; Wheatland, Chloe
This article addresses the growing trend of crowdfunding for unproven stem cell-based treatments. Our analysis uses quantitative and qualitative data collected from two popular fundraising sites to examine how these sites are used to fund purported stem cell 'treatments' or 'therapies'. In addition to mapping the use and success of these online campaigns by people with different health conditions in different locations, we consider the breakthrough restitution story as a key narrative that campaign organisers use to solicit donations. We argue that crowdfunding is a rapidly growing digital space where 'truths' about experimental treatments are constituted and a politics of evidence is unfolding. These developments are to the potential financial benefit of crowdfunding platforms and businesses offering unproven stem cell-based interventions, and to the potential detriment of patients and their supporters.